Bilateral Radial Head Fracture with Unilateral Terrible Triad Injury in a Military - Bennani, Mourad; Guenbdar, Mouad; Cherrad, Taoufik; Zejjari, Hassan; Louaste, Jamal; Amhajji, Larbi (Archives of Clinical and Medical Case Reports, 2023)
Background: The combination of coronoid process fracture, radial head fracture, and elbow dislocation has earned the moniker “terrible triad” by virtue of its challenging treatment and historically poor outcomes. Bilateral radial head fracture with unilateral terrible triad injury is an unprecedented presentation. It raises questions regarding the mechanism of injury, the surgical indication and the rehabilitation program. Case Presentation: We report a case of a 29-year-old man presenting a unilateral terrible triad injury of the right elbow and a left radial head fracture after he fell off his motorcycle. The patient underwent open reduction and internal fixation of the radial head with repair of the lateral collateral ligament for the right elbow while the left radial head fracture was treated by a short-term immobilization in a posterior splint. We have reached good results 2 years after the injury: The Mayo Elbow Performance Score was 100 for both elbows. Conclusion: The few available data suggest that bilateral elbow injury involving a terrible triad occurs mainly in male young patient as a result of a high energy trauma. Bilateral radial head fracture with unilateral terrible triad injury is unprecedented. Well adapted surgical indication followed by optimal rehabilitation program are the two keys to obtain good results.